ANALISIS RASIO LIKUIDITAS, PROFITABILITAS DAN LEVERAGE PADA PT. TRINITY AUTO SAMARINDA - -, Sri Wahyuni (EKONOMIA, 2019)
The analytical tool used to measure liquidity ratios includes the current ratio, to measure profitability ratios the analytical tool used is return on assets, while to measure leverage the analytical tool used is the debt ratio. Based on the results of analysis and discussion, the financial performance of PT. Trinity Auto Samarinda in terms of liquidity ratio, profitability and leverage decreased from 2014 to 2016. The company's current ratio in 2014 was 3.92%, increased in 2015 to 5.75%, but in 2016 it decreased to 2.17%. The return on assets ratio decreased by 7.71% in 2014 to 2.42% in 2015, then to 0.70% in 2016. The results of the debt ratio study showed that 2014 amounted to 17.50%, increasing to 32, 81% in 2015 and in 2016 it rose again to 48%. Thus with this, the hypothesis that researcher stated earlier is: "There has been an increase in company performance at PT. Trinity Auto Samarinda in the period 2014 to 2016 in terms of analysis of liquidity ratios, profitability and leverage" was rejected. This is because most of results analysis of ratio declined from 2014 to 2016.